EFEKTIVITAS PENDEKATAN REALISTIC MATHEMATICS EDUCATION BERBASIS SOAL AKM DALAM MENINGKATKAN KEMAMPUAN NUMERASI SISWA UNTUK MENDUKUNG SDGS 4 DI SD X KABUPATEN MAGETAN - Isna Qurrotun Aini; Aulia Luthfi Ramadhani; Masayudia Anisa Triyanti; Novi Leny Rahmadhani; Jona Pradigda; Marshya Lutvianes; Iwan Maulana (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
Numeracy skills are essential competencies of the 21st century that play an important role in supporting the achievement of quality education as stated in the Sustainable Development Goals (SDGs) 4. However, the results of the Minimum Competency Assessment (AKM) show that the numeracy skills of elementary school students in Indonesia are still relatively low, which is caused by mathematics learning that tends to be abstract and teacher-centered. This study aims to analyze the effectiveness of the Realistic Mathematics Education (RME) approach based on AKM questions in improving students' numeracy skills. The study used a quantitative method with a quasi-experimental design of one group pretest-posttest. The subjects were students of Elementary School X in Magetan Regency. The instrument used was a validated AKM-based numeracy test, while data analysis was carried out through paired sample t-test statistical tests and N-gain calculations. The results showed that the average student score increased from 57.9 in the pretest to 75.6 in the posttest, with a significance value of 0.000 (<0.05) indicating a significant increase. The N-gain value of 0.42 is in the moderate category, indicating that this approach is quite effective. This finding implies that integrating RME and AKM questions can be an innovative strategy for improving student numeracy while supporting the achievement of SDG 4.